A Meta Analysis: Effectiveness of Telemedicine to Improve Self-Care in Patients with Hearth Failure - Ersananda, Audria; Prasetya, Hanung; Ichsan, Burhannudin (Journal of Health Policy and Management, 2024)
Background: Modern and sophisticated self-care education programs such as web-based methods and wireless networks can make changes in patient behavior to improve self-care management. Telemedicine is a potential alternative to continue providing patient health services by minimizing the risk of exposure and physical contact. This study aims to investigate relevant primary studies in order to assess the effectiveness of telemedicine to improve self-care in heart failure patients. Subjects and Method: This study used a systematic review and meta-analysis with PICO namely, P: Patients with heart failure, I; using telemedicine, C: not using telemedicine, O: increasing self care for heart failure patients. By searching for articles in 3 databases namely PubMed, Google Scholar, Cochrane which were published from 2013 to 2023, entering the following keywords (“Heart Failure” OR “congestive heart failure”) AND (Telemedicine OR “electronic health record” OR mHealth OR “ mobile health” OR “mobile app” OR “telehealth” OR “healthcare system information”) AND “self care” AND “randomized controlled trials”. Articles were selected using PRISMA flow and data analysis using the Review Manager 5.3 application. Results: Meta-analysis was carried out on 9 primary studies using RCT study designs from several countries such as Canada, the United States, Colombia, Australia, Hong Kong, Finland with a total sample size of 1.018. The processed meta-analysis data found that telemedicine is effective for improving self-care in heart failure patients, and is statistically close to significant. Heart failure patients who received telemedicine-based education had an average self-care value of 0.33 SMD units higher than those who did not receive the intervention (SMD= 0.33; 95% CI= 0.15 to 0.52; p= 0.004). Conclusion: Telemedicine is effective for improving self care in heart failure patients. Keywords: Heart Failure, Self Care, Telemedicine. Correspondence: Audria Ersananda, Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah. Email: audriaersa@gmail.com. Mobile: 082233999407.